Emotion regulation and cortisol response to the still-face procedure in preterm and full-term infants. (July 2022) - Ginnell, Lorna; O'Carroll, Sinéad; Ledsham, Victoria; Jiménez Sánchez, Lorena; Stoye, David Q.; Sullivan, Gemma; Hall, Jill; Homer, Natalie Z.M.; Boardman, James P.; Fletcher-Watson, Sue; Reynolds, Rebecca M.
Abstract: In infancy, stress responses and emotion regulation are often coupled. Both are impacted by prematurity, though their relationship to one another in the case of infants born preterm is not fully understood. We investigated emotion regulation behaviours, cortisol reactivity and recovery and coupling between emotion regulation and cortisol reactivity to and recovery from a stressor in preterm infants. 53 preterm and 67 full-term infants with mean (range) gestational age at birth 29 +3 (24 +0 -31 +6 ) and 39 +3 (36 +2 -42 +0 ) weeks respectively were exposed to a socio-emotional stressor, the still-face (SF) paradigm, at 9 months of age (corrected for prematurity). The duration of negative affect and self-comforting behaviours exhibited in response to the SF, coded from a 10-minute video-taped interaction, were compared between groups. Saliva was collected from a subset (20 preterm, 24 term infants) at three timepoints: pre-SF and 20- and 30-minutes post SF. Cortisol concentrations at each timepoint were compared between groups. Associations between behavioural measures and cortisol concentrations were explored. There was no significant difference in duration of self-comforting behaviour between preterm and term infants. Preterm infants spent a significantly smaller proportion of time in a negative affective state compared to term infants (0.18 vs 0.25 s, p = 0.03). Salivary cortisol concentration was significantly higher in the preterm compared to the term group 30 min post SF (2.85 vs 1.77 nmol/L, p = 0.009), though findings were no longer significant after adjusting for time of day of sampling and socioeconomic deprivation. After controlling for time of day, greater negative affect was correlated with higher cortisol concentration 30 min post SF in the full-term (r = 0.58, p = 0.004) but not the preterm group (r = −0.01, p > 0.05). Our findings suggest altered response to an acute stressor in preterm infants, manifesting as a muted emotional response, and a lack of coupling between endocrine and behavioural stress response. Replication studies in larger samples would help to further understand biological stress repose in preterm infants and its relationship to behaviour, time of day and deprivation. Highlights: Preterm compared to term infants display less negative affect during the still-face. Preterm infants lack coupling between emotion regulation and stress response. Socioeconomic deprivation may influence cortisol response to the still-face.